Domestic sources of Russian foreign policy and their impact on Russia's relations with Azerbaijan - Shirinov, Rashad. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
The proposed thesis analyses Russian foreign policy during 90-s. The focus of the study is the domestic actors inside Russian politics and their impact on Russia's relations with its Near Abroad, particularly with its southern neighbour Azerbaijan. Foreign policy analysis is accepted as the method or research. Theoretical framework of foreign policy provides for our better understanding of complex relations within Russian government and how they are related to the world. Chronologically, we have studied decision-making during Soviet time hypothesizing that some features of "Soviet behavior" could also be continuing in current Russian politics. Perestroika and regime change in Russia gave birth to new actors who were in support of Russia's cooperative relations with West and other countries. These new forces encountered a difficult task of competing with older ones with more hostile agenda and discourse. Russia's Azerbaijan policy is analysed against the background of this fundamental transformation of Russian state, politics, society, economy and identity. Traditional attitudes of mind and new pragmatic approaches, mths and reality, political ideas and economic profit-these all are two contradictory sides of Russian foreign policy towards Azerbaijan during last decade.